Qualidade do leite e da silagem de milho em sistemas de produção leiteiros da região Oeste do Paraná e inclusão de milho quebrado na dieta de vacas em lactação - Werle, Caroline Hoscheid (2020)
The first article aimed to assess the volume of milk intake in the 12-year period of a dairy industry, verifying seasonality in volume and quality throughout the year, in addition to checking compliance with current regulatory instructions. In the analysis of main components, dimension one was composed by the number of producers and dimension two by the total volume of milk received on the platform. The seasons influence the composition of milk, mainly according to the quantity and quality of the diet offered. The milk received att the platform still does not meet the requirements of the normative instructions, requiring greater technical monitoring of them to improve the parameters of CPP and CCS. The second article aimed to verify the influence of the quality of corn silage on the physical-chemical composition of milk and milk production. In dimension one, the composition variable was milk quality and in dimension two, the components of corn silage. There was no evidence of a correlation between the physical-chemical composition of corn silages and the composition and quality of milk in properties in the municipality of Marechal Cândido Rondon participating in this study. The third article aimed to evaluate the level of inclusion of broken corn in the diet of lactating cows. Twelve lactating Holstein cows were used, distributed in triple Latin square 4x4, fed diets containing levels of 0%, 10%, 20% and 30% of broken corn inclusion in the MS. No effects were observed for the consumption of nutrients, except for the consumption of ether extract. Regarding digestibility, the ether extract and neutral detergent fiber showed a decreasing linear effect for the inclusion levels. Milk production was not influenced by the inclusion levels of broken corn, but the protein showed an increasing linear effect and the NUL decreasing linear effect. The economic return was greater for diets containing broken corn. The use of broken corn in the concentrate of lactating cows can be carried out at levels of up to 30%.